Phénomènes de discordance entre morphologie et syntaxe : de la zizanie dans le collectif ! - Blandine Pennec (Corela)
This paper examines phenomena of discordance between morphology and syntax, such as the plural concord of verbs with nouns which are morphologically in the singular, or vice versa. The principle of sylleptic agreement, which is used to account for such phenomena, is not sufficient to describe the great variety of cases, and it is thus necessary to identify the reasons for those sylleptic agreements. Besides the case of collective nouns (for which we propose a typology), this study deals with the concords that take place with N1 of N2 expressions, in which N1 evokes a multiplicity of elements, and it also examines the concords characterizing nouns of firms or companies. This paper also shows that a certain number of mismatches between morphology and syntax can be explained thanks to phenomena of metonymy, ellipsis or thanks to the use of epicene nouns. Some expressions used to express quantification also lead to surprising concords, which can either be in the singular or in the plural according to the context, and this study tries to account for the possibility of such alternations.